Estudo sobre a percepção acerca de aspectos geomorfológicos da paisagem pelo indivíduo com deficiência visual - Oliveira, Talitha Tomazetti Ribeiro de (2016)
The teaching Geography for people with visual impairment is a great challenge, because many of the geographical concepts studied in class are considered as visual understanding, the relief and landscape study, for example, become much more accessible when the student visually assimilates the way these concepts are presented. Therefore you can say that the student who is blind has disadvantages on this knowledge acquisition. And in this case the use of teaching resources adapted to the necessities of this student is essential, so that, he will be able to learn with more ease. The use of teaching resources adapted to the student‟s necessities does not assure him to recreate what is being exposed, because each individual case has its differences that should be respected, although much research developed with this subject test positive for the most part. From this understanding, arises the necessity not only to measure how the materials are made and if they are efficient in relation with the student with visual impairment, but also how the concepts are being understood by him. This research aims to understand how the student, even if with visual impairment, realizes and assimilates the geographic space he is introduced in. In this case the research is based on a case study and refers to the Rio Grande do Sul‟s geomorphological landscape. General purpose of this research analyzes how the student with visual impairment understand the Rio Grande do Sul‟s geomorphological landscape from his perception, by the representation resource constructed. To achieve desired results, it has developed a visual and tactile language (adapted learning materials), and it has applied this material to the student with visual impairment to obtain data which would allow us to understand the way that this student has interacted with the resource, then we could find that the use of the adapted resources with blind students has improved their learning, and the student appropriates references from their daily lives to understand the meaning of landscape and space.